Inhibition of the human proteasome by imidazoline scaffolds - Azevedo, Lauren M. (2013)
The proteasome has emerged as the primary target for the treatment of multiple myeloma. Unfortunately, nearly all patients develop resistance to competitive-type proteasome inhibitors, such as bortezomib. Herein, we describe the optimization of non-competitive proteasome inhibitors to yield derivatives that exhibit nanomolar potency (compound 46, IC(50) 130 nM) towards proteasome inhibition and overcome bortezomib resistance. These studies illustrate the feasibility of the development of non-competitive proteasome inhibitors as additives and/or alternatives to competitive proteasome inhibitors.